Interventions in animal health: economic analysis of the adoption of herd health risk management programmes in smallholder dairy farms in central Thailand - Hall, D.C.; Ehui, Simeon K.; Shapiro, Barry I. (International Livestock Research Institute, 2002)
This paper examines the adoption of two herd health control programmes designed for dairy smallholders in Central Thailand - for mastitis and for reproductive disease. The impact of adoption on private and social welfare is measured using the Policy Analysis Matrix. For adopters of the mastitis and reproductive health programmes, milk production increased by 173% and 48% respectively. Annual returns per cow were 166% and 154% greater respectively than the control group returns. Disease was significantly reduced on all adopter farms, and highest reductions were seen on adopter farms. It is demonstrated that an increase in social profits should occur owing to social revenues increasing at a greater rate than social costs. The policy implications of this observation are discussed.